ANALISA KEBUTUHAN JEMBATAN PENYEBERANGAN ORANG DI KOTA BANDAR LAMPUNG, LAMPUNG - Aditya Mahatidanar Hidayat (Universitas Bandar Lampung, 2018)
The existence of pedestrians would need the facility for pedestrians, crossing street as the people crossing bridge ( bridge ), where the bridge mounted when required no a meeting between the current walkers and traffic flow.That pedestrians want to use bridge must all be ensured security and distance increased are not going too far.The purpose of this research is analyzing the needs of the people crossing bridge in the way of legal because lampung city based on the calculation on, the volume of vehicles highest a month 8539 junior / hours with the 403 waders per hour him and speed rata-rata 28,4 km / hours.With the data collected and based on the results of the analysis representing day and rush hour road users in one week and in concluded clearly that it is supposed at roads legal because precisely in front of Pasar Koga and Advent Hospital built bridge people to pedestrian